Criticality in the Healthy Brain - Shi, Jifan; Kirihara, Kenji; Tada, Mariko; Fujioka, Mao; Usui, Kaori; Koshiyama, Daisuke; Araki, Tsuyoshi; Chen, Luonan; Kasai, Kiyoto; Aihara, Kazuyuki (Frontiers in Network Physiology, 2022)
The excellence of the brain is its robustness under various types of noise and its flexibility under various environments. However, how the brain works is still a mystery. The critical brain hypothesis proposes a possible mechanism and states that criticality plays an important role in the healthy brain. Herein, using an electroencephalography dataset obtained from patients with psychotic disorders (PDs), ultra-high risk (UHR) individuals and healthy controls (HCs), and its dynamical network analysis, we show that the brain of HCs remains around a critical state, whereas that of patients with PD falls into more stable states. Meanwhile, the brain of UHR individuals is similar to that of PD in terms of entropy but is analogous to that of HCs in causality patterns. These results not only provide evidence for the criticality of the normal brain but also highlight the practicability of using an analytic biophysical tool to study the dynamical properties of mental diseases.